Frequencies of VKORC1-1639G>A and rs397509427 in Patients on Warfarin and Healthy Syrian Subjects - Yara Altawil; Lama A. Youssef (Hindawi-Wiley, 2023)
Background. Vitamin K epoxide reductase complex subunit 1 (VKORC1) gene encodes a key enzyme with multiple cellular activities, namely, the reduction of vitamin K to its active form. VKORC1-1639G>A (rs9923231) is a common single nucleotide polymorphism with a crucial impact on warfarin dosing and possibly other physiological functions. This study aimed at investigating the frequencies of VKORC1-1639G>A alleles and genotypes in Syrian healthy subjects and patients on warfarin for different indications. Methods. A total of 138 individuals were enrolled in this cross-sectional study. Genomic DNA was extracted from both patients on warfarin and healthy subjects, and polymerase chain reaction (PCR) specific amplicons were genotyped via standard sequencing which also allowed the detection of rs397509427. Comparisons of -1639G>A frequency with other populations were drawn. Results. Of 94 patients on warfarin, 53 (56.38%) were with idiopathic venous thromboembolism (VTE). Despite comparable frequencies of the -1639A allele (47% and 50%), the AA and GA genotypes were at disparate frequencies of 93.2% versus 79.8% in the healthy subjects (n=44) versus patients on warfarin, respectively. Carriers of the GG genotype were at a four-fold increased risk of VTE in comparison with those of the AA and GA genotypes (odds ratio OR=4, 95% CI=1.105−13.6, P=0.0469). All study subjects were wild-type for the rs397509427 variant. Conclusions. Our results prove a high -1639A prevalence in Syrian healthy subjects and patients on warfarin at frequencies comparable to other Mediterranean and Middle Eastern populations. The A allele carriers are at a lower VTE risk, whereas a global prevalence gradient of the G allele is suggested to be associated with VTE risk.